Pseudomonas aeruginosa renews its virulence factors. Issue 5 (25th August 2016) - Huber, Philippe; Basso, Pauline; Reboud, Emeline; Attrée, Ina
Summary: Highly divergent strains of the major human opportunistic pathogen Pseudomonas aeruginosa have been isolated around the world by different research laboratories. They came from patients with various types of infectious diseases or from the environment. These strains are devoid of the major virulence factor used by classical strains, the Type III secretion system, but possess additional putative virulence factors, including a novel two‐partner secretion system, ExlBA, responsible for the hypervirulent behavior of some clinical isolates. Here, we review the genetic and phenotypic characteristics of these recently‐discovered P. aeruginosa outliers.